2023
DOI: 10.1111/agec.12778
|View full text |Cite
|
Sign up to set email alerts
|

Gender pay gaps in economics: A deeper look at institutional factors

Abstract: Using rich data on graduate tenure-track faculty, we explore the gender pay gap in academic departments of economics and agricultural/applied economics and the differences between them. We find that the gender pay gaps in economics and agricultural/applied economics are 8.3% and 4.1%, respectively, controlling for faculty rank, experience, and university affiliation. The gender pay gap increases with rank and varies across institutions. Productivity is an important determinant of wages but it explains little o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…To ensure that our results held for the whole data panel, we also removed the rank controls in column 6 and found that the estimated coefficient for female academics was even larger and more significant (0.04, with a t-statistic of 2.91). 2 These findings are consistent with the aggregate evidence on the unexplained variation in the gender pay gap (Grove et al 2011;Maitra et al 2021;Kim et al 2023). We contribute to this literature by suggesting that the wage differential may not result from taste-based discrimination in an academic setting, but rather that the salary gap can be explained by factors related to teaching and research productivity.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…To ensure that our results held for the whole data panel, we also removed the rank controls in column 6 and found that the estimated coefficient for female academics was even larger and more significant (0.04, with a t-statistic of 2.91). 2 These findings are consistent with the aggregate evidence on the unexplained variation in the gender pay gap (Grove et al 2011;Maitra et al 2021;Kim et al 2023). We contribute to this literature by suggesting that the wage differential may not result from taste-based discrimination in an academic setting, but rather that the salary gap can be explained by factors related to teaching and research productivity.…”
Section: Resultssupporting
confidence: 80%
“…The dependent variable is the log of the annual salary, for an individual i in year t. The primary coefficient of interest is β 1 , which represents the estimated wage gap for female (Female) relative to male academics. We then followed prior literature (i.e., Ward 2001;Sayre et al 2000;Chen and Crown 2019;Smith-Carrier et al 2021;Kim et al 2023) and added a set of control variables P it as proxies for productivity for an individual i in year t (obtained from Google Scholar, ResearchGate, and the most recent individual CVs), which included the following (up to year t): the log of citations (Cite), the number of books (#Books), the number of chapters/cases (#Ch/Ca), the number of publications in peer-reviewed journals (#PR Pubs), and the number of publications in journals on the Financial Times list (#FT Pubs); a set of control variables F it as proxies for full-time equivalency, which included (for year t) an indicator variable for part-time (PT), the number of semesters of unpaid leave (UL), the number of semesters of study leave (SL), the number of courses taught as an overload or bought out and not taught (OL), and the number of semesters of parental leave (PL); and a set of control variables X it , which included ethnicity controls (indicators for race/ethnicity-African American, Indian, Asian/Pacific Islander, Native American, and Other, including multiple and undisclosed ethnicities, with Caucasian as the omitted category), prior experience controls (indicators for prior academic experience--Prior AE, and prior work experience-Prior WE, and the number of years employed by SFU-#SFU), education controls (indicators for PhD degree-PhD, professional designation and certificate-Des/Cert), and rank and promotion controls (indicators for faculty rank: Assistant-Assist Prof, Associate-Assoc Prof, and Full-Full Prof, with Lecturer and Other-Lect/Other as the omitted category; and indicators for promotions from Lecturer, Assistant, and Associate levels). Table 1 presents the definitions for all the variables utilized in our analysis.…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, Bandiera et al (2016) examined the gender pay gap at the LSE using internal research productivity scores, concluding that controlling for predicted REF scores had minimal effect on the pay gap, indicating lower pay for women with the same level of research productivity. Thus, as noted by Kim et. al.…”
Section: Sources Of Biassupporting
confidence: 61%